Efficacy and safety of tranexamic acid in cervical spine surgery: a systematic review and meta-analysis - Luo, Hua; Yang, Yu; Wang, Zhitao; Ma, Lingping; Xie, Chengxin (Frontiers in Neurology, 2024)
Background Tranexamic acid (TXA) is an antifibrinolytic drug associated with reduced blood loss in a range of surgical specialties. This meta-analysis aimed to compare the efficacy and safety of TXA in cervical surgery, focusing on its effects on intraoperative blood loss and related outcomes. Methods We searched the PubMed, EMBASE, Medline, and Cochrane Library databases to identify all literature related to TXA used in cervical spinal surgery. Intraoperative blood loss, postoperative drainage volume, total blood loss, postoperative hematological variables, and complications were analyzed. Results Eight trials met the inclusion criteria. The pooled results showed that intraoperative blood loss, total blood loss, and postoperative drainage volume were significantly lower in the TXA group than in the control group. The hemoglobin and hematocrit on postoperative day 1 was significantly higher in the TXA group than in the control group. There was no significant difference in complications between the two groups. Conclusion The available evidence indicates that TXA effectively reduces blood loss in cervical spinal surgery while maintaining a favorable safety profile, without increasing associated risks. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023459652.